Sending Nudes: Sex, Self-Rated Mate Value, and Trait Machiavellianism Predict Sending Unsolicited Explicit Images - March, Evita; Wagstaff, Danielle L. (Frontiers in Psychology, 2017)
Modern dating platforms have given rise to new dating and sexual behaviors. In the current study, we examine predictors of sending unsolicited explicit images, a particularly underexplored online sexual behavior. The aim of the current study was to explore the utility of dark personality traits (i.e., narcissism, Machiavellianism, psychopathy, and sadism) and self-rated mate value in predicting attitudes toward and behavior of sending unsolicited explicit images. Two hundred and forty participants (72% female; Mage = 25.96, SD = 9.79) completed an online questionnaire which included a measure of self-rated mate value, a measure of dark personality traits, and questions regarding sending unsolicited explicit images (operationalized as the explicit image scale). Men, compared to women, were found to have higher explicit image scale scores, and both self-rated mate value and trait Machiavellianism were positive predictors of explicit image scale scores. Interestingly, there were no significant interactions between sex and these variables. Further, Machiavellianism mediated all relationships between other dark traits and explicit image scale scores, indicating this behavior is best explained by the personality trait associated with behavioral strategies. In sum, these results provide support for the premise that sending unsolicited explicit images may be a tactic of a short-term mating strategy; however, future research should further explore this claim.